CCA-C RETENTION & PENETRATION IN PINO CHUNCHO WOOD (Schizolobium amazonicum Huber. Ex Ducke) FOR NON-STRUCTURAL USE - Trujillo Cuellar, Florencio Teodoro; Aguirre Cortez, Alex Alfredo; Klitzke, Ricardo Jorge; Pereira Da Rocha, Marcio; Gonzales Mora, Hector Enrique; Araujo Flores, Martin (Floresta, 2021)
The quality of wood treatment, by retention and penetration of CCA-C was evaluated in pino chuncho wood (Schizolobium amazonicum Huber. Ex Ducke), for non-structural use indoors (4 kg/m-3) and outdoors (6.4 kg/m-3) by the simple dipping (immersion) and full-cell methods. Thus, five trees from a 23-year-old plantation were randomly selected, producing 64 samples with a cross section of 50 mm x 50 mm and 500 mm long with 15% moisture content. The simple immersion treatment of 2 to 14 days showed average retentions between 1.5 to 3.7 kg/m-3, similar to results by the full-cell method with a pressure of 120 lb./in.-2 by 10, 20 and 30 minutes of treatment showing average retentions from 3.2 to 3.9 kg/m-3; during both methods penetration of a partial vascular type preservative was applied. With 150 lb./in.-2 and 10, 20 and 30 minutes of treatment, retentions between 5.1 and 5.9 kg/m-3, with irregular partial preservative penetrations were observed. Finally, with 180 lb./in.-2 for 10, 20 and 30 minutes of treatment, regular total preservative penetrations, and retention of 5.6, 7.4 and 8.1 kg/m-3 respectively, were achieved, suitable for non-structural use indoors (with 10 minutes), and indoors and outdoors (with 20 and 30 minutes). The influence of increased pressure on increased retention with the same treatment time was significant, unlike increasing the treatment time at the same treatment pressure. Keywords: Immersion, preservation treatment, full-cell method, treatment quality